Դավիթ Անհաղթի «Բարձրացուցէք»-ի՝ Ներսես Շնորհալու մեկնությունը - Արմինե Մելքոնյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
«Панегирик Богоприимному Святому Кресту» (Бардзрацуцек) выдающегося армянского философа и богослова V-VI веков Давида Анахта (Непобедимый) был включен в программу средневековых вузов Армении и имел большое влияние на армянскую литературу. Армянские авторы сочиняли «причины» и комментарии кэтойработе. В данной статье на основе древних рукописей представлен доселе неопубликованный комментарий НерсесаШнорали к «Панегирику», а также его стихосложение. НерсесШнорали создал свой «Комментарий» по просьбе автора XII века ВарданаАхбатеци, который написал «причину» к «Панегирику». “Encomium on the Theoleptic Holy Cross” (Bardzratsutsek) by the 5th-6th century Armenian prominent philosopher and theologian David the Invincible was included in the programme of medieval high schools in Armenia and had great infl uence on the Armenian literature. Armenian authors wrote ‘causes’ and commentaries on it. In this article the extensive and yet unpublished commentary on the Encomium as well as its versifi cation by Nerses the Graceful are presented based on the ancient manuscripts. St. Nerses created his Commentary at the request of the 12th century author Vardan of Haghbat, who wrote а “cause” on the Encomium.
Keywords: Literature; Christianity; Criticism